The Helpful Role of CD10 and Hormonal Receptors Co-Expression in the Histologic Diagnosis of Catamenial Pneumothorax. (September 2019) - Mataca, Ema; Rossi, Giulio; Colby, Thomas V.
The histology in cases of primary spontaneous pneumothorax is generally nonspecific, but a careful examination, taking into account clinical data, may reveal subtle tissue alterations leading to a specific diagnosis in cases that might otherwise be taken as primary and spontaneous. In this article, we describe 3 cases of catamenial pneumothorax histologically demonstrated by the presence of scattered and submillimeter aggregates of bland-looking spindle endometrial stromal cells (so-called "stromal endometriosis") into the visceral pleural layer. The use of CD10 and estrogen and progesterone receptors in lung resection specimens from young women experiencing recurrent pneumothorax is extremely helpful in disclosing endometriosis and confirming a diagnosis of catamenial pneumothorax. A review of the literature on this topic is also presented.